IMPROVEMENT OF TREASURY CONTROL OVER BUDGET EXPENDITURE (World of finance, 2023)
Introduction. In the conditions of the war period, it is important for the financial system of Ukraine to effectively use budget resources, which are extremely necessary to ensure defense capability and make timely social payments to the population. Compliance with budget legislation, economy and reasonableness in spending contribute to the preservation of budget resources and directing them only to urgent needs. The above actualizes the issue of improving approaches to treasury control at the stage of registration of budget obligations of managers of budget funds.The purpose of the article is to analyse the state of compliance with the legislation by the participants of the budget process during the implementation of expenditures and justify proposals for improving treasury control.Results. In the process of analyzing the application of measures of influence to the participants of the budget process for violations of budget legislation, in particular issuing warnings about improper implementation of budget legislation and stopping operations with funds on customer accounts, a decrease in the number of such violations in 2022 was revealed, which indicates an increase in budget discipline. It was established that most of the violations, namely 93%, are observed during the registration of budget obligations. The need to strengthen treasury control over the expediency and legality of spending budget funds at the stage of registering budget liabilities has been proven.Conclusions. It is proposed to expand the list of powers of the Treasury bodies in terms of verification of justification of the feasibility of purchases that managers of budget funds plan to carry out, as well as strengthening control over the prevention of registration of budget obligations under procurement contracts, which may be declared null and void in accordance with the law. It is emphasized that the strengthening of treasury control at the previous stage before payment under contracts is more effective than after the implementation of operations with budget funds.